The use of photogrammetry techniques to evaluate the construction project progress - Ahmed Memon, Zubair; Abd. Majid, Muhd Zaimi; Mustaffar, Mushairry (Penerbit UTM Press, 2006)

(untitled)
The modeling of 3D objects from image sequence is a challenging problem and has been an important research topic in the areas of photogrammetry and computer vision for many years. Photogrammetry is the science of calculating 3D object co-ordinates from image and provides a flexible and robust approach for measuring the static and dynamic characteristics for construction management. This paper discusses the experience in Construction Technology and Management Centre (CTMC), Universiti Teknologi Malaysia (UTM) in adapting photogrammetry methods for specific problems in the construction industry and outlines the principles of close-range photogrammetry in evaluating the progress of construction projects. There is a need to use the principles of close-range photogrammetry to evaluate the progress of construction project and to develop the actual progress bar chart. The fundamental task of photogrammetry is to rigorously establish the geometric relationship between the image and the object, as it existed at the time of imaging event. One such software application is PhotoModeler Pro version from the Canadian company Eos System has been suggested to extract the 3D features from 2D images. The approach described in this paper demonstrates the use of digital photogrammetry as a complementary method, which describes the 3D features extraction procedure in detail and highlights the qualitative control that can be achieved during the construction. The technique uses mainly off-the-shelf digitalcamera and software technologies that are affordable to most organisations and able to provide acceptable accuracy.